2020–2021 Vegetable Production Handbook: Chapter 6. Cole Crop Production - Lincoln Zotarelli; Peter J. Dittmar; Nicholas S. Dufault; Bonnie Wells; Johan Desaeger; Eugene J. McAvoy; Qingren Wang; Christian F Miller (EDIS, 2020)
This chapter covers production of cole crops and Asian crucifers, including broccoli, cabbage, cauliflower, Chinese broccoli, Chinese cabbage, Chinese mustard (bok choy), kohlrabi, lobok/daikon, collards, kale, mustard, and turnip.